Single-unit activity in the anterior claustrum during memory retrieval after trace fear conditioning - Sewon Park; Kuenbae Sohn; Donghyeon Yoon; Junghwa Lee; Sukwoo Choi (PLoS ONE, 2025)
We have recently identified a group of claustral neurons that continuously maintain information associated with a fear-conditioned stimulus (CS) for at least tens of seconds, even after the CS has ceased. This “online state” refers to the persistent maintenance of threat-associated information, enabling it to be actively processed even after the threat has terminated. This state may involve reciprocal interactions of the claustral neurons with brain regions involved in decision-making, motor preparation, and adaptive behavioral responses. If these claustral neurons truly encode the online state, their function should remain independent of the modality of the threat stimulus or the specific defensive behavior exhibited. In this study, we used a tone cue and monitored freezing behavior in trace conditioning, in contrast to the light cue and escape behavior used in our recent study. During the retrieval test of trace conditioning, a subset of rostral-to-striatum claustrum (rsCla) neurons exhibited sustained activity in response to the CS, particularly during the trace interval. Importantly, we found a positive correlation between the activity of rsCla neurons and the magnitude of freezing during the trace interval, when intervals without freezing were excluded. Thus, this subset of rsCla neurons appears to exhibit the characteristics of ‘online neurons’ during memory retrieval following trace conditioning.